2005
DOI: 10.1021/ie049196s
|View full text |Cite
|
Sign up to set email alerts
|

Experiments and Numerical Simulations of Supercritical Fluid Extraction for Hippophae rhamnoides L Seed Oil Based on Artificial Neural Networks

Abstract: In this paper, a supercritical fluid extraction setup with an extraction volume of one liter was established with which Hippophae rhamnoides L seed oil was extracted using supercritical CO 2 . The experiments show that many factors have an impact on the oil yield, such as extraction pressure, temperature, and fluid flow rate, as well as seed particle size and filling quantity. For the extraction process of H. rhamnoides L seed oil, the recommended conditions were as follows: extraction pressure of 20-30 MPa, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Thus, the predicted recovery rates for oil, vitamin E and carotenoids by supercritical CO 2 extraction under optimum conditions were 96.5%, 125.6% and 98.7%. Oil recoveries of 65-90% from the seed and pressed pulp of sea buckthorn by SC-CO 2 extraction have been reported (Yakilimishen et al, 2005;Yin, Xu, Wei, & Wang, 2005), which were lower than the predicted recovery under optimum conditions in the present study. The greater than 100% recovery for vitamin E by supercritical CO 2 extraction is likely due to the heatinduced loss of vitamin E occurred during the Soxhlet extraction which was conducted at 70 1C.…”
Section: Optimization Of Extraction Conditioncontrasting
confidence: 74%
“…Thus, the predicted recovery rates for oil, vitamin E and carotenoids by supercritical CO 2 extraction under optimum conditions were 96.5%, 125.6% and 98.7%. Oil recoveries of 65-90% from the seed and pressed pulp of sea buckthorn by SC-CO 2 extraction have been reported (Yakilimishen et al, 2005;Yin, Xu, Wei, & Wang, 2005), which were lower than the predicted recovery under optimum conditions in the present study. The greater than 100% recovery for vitamin E by supercritical CO 2 extraction is likely due to the heatinduced loss of vitamin E occurred during the Soxhlet extraction which was conducted at 70 1C.…”
Section: Optimization Of Extraction Conditioncontrasting
confidence: 74%
“…A similar effect was previously reported for borage oil [4], and these authors found that, when operating at pressures under 200 bar, the extraction yield was higher at 283 K than at 313 and 333 K. Kotnik et al [2] found the same behavior for borage seeds when the extraction was carried out at 313 K and 200 bar; Roy et al [13] reported a decrease in the sunflower oil extraction yield with an increase in temperature at 200 bar, but at higher pressures (300, 400 bar) the extraction yield increased with increasing temperature. A decrease in the extraction yield with increasing temperature at lower pressures was also reported for the oil extraction from Hippophae rhamnoides [14], okra [15], and fennel [16] seeds. At lower pres- sures, lower temperatures are desirable since the change of solvent density with temperature is more marked than the change in the solute vapor pressure.…”
Section: Extraction Of Borage Seed Oil By Sc-cosupporting
confidence: 64%
“…There are various types of learning methods for neural networks, whereby one of the most applied methods is the backpropagation learning rule. Neural networks have been applied to several SFE processes in predicting the yield of extraction [46][47][48][49][50][51] , initial slope 49 , and solubility [52][53][54] . Table-2 lists some of the works that applied ANNs in the SFE of plants.…”
Section: Predictive Toolsmentioning
confidence: 99%